COMPARATIVE STUDIES ON EFFECT OF SEED ENHANCEMENT TREATMENTS ON VIGOUR AND FIELD EMERGENCE OF DESI AND KABULI CHICKPEA ( ABULI CHICKPEA (CICER ARIETINUM L.) - AMARENDRA KUMAR , RAKESH KUMAR, MUKESH KUMAR; RAJBIR YADAV, SHIV KUMAR YADAV; KUMARI, AND HEMLATA (The Bioscan, 2016)
A study was conducted to assess the comparative effect of seed enhancement treatment on seed vigour, abnormal seedling, and field emergence of desi and kabuli type of chickpea (Cicer arietinum L.). Desi cultivar Pusa 256, and Kabuli cultivar Pusa1053, each of fresh, 2yrs old and 4 yrs old lots were taken for seed enhancement treatments viz; osmopriming, halopriming, fungicidal, botanical and polymer coating alone and in combination with thiram and neemoil. It was observed that seed treatment with thiram alone or in combination with polymer (PVP or PEM) significantly enhances germination and field performance. The indirect test for seed vigour i.e. Electrical Conductivity (EC) test was also conducted and observed that it was very significantly correlated with first count, vigour index I and II and field emergence. The storage studies under ambient conditions indicated that desi variety maintained satisfactory germination and field performance upto 2 years while kabuli variety suitable for sowing in maximum upto subsequent year stored under ambient condition.